An inclusive community at the turn of the millenium: AMRITA - Boros, Julianna (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In the mid-1990s, one of the first initiatives to promote school success in Hungary was the career guidance programme for Roma students run by the Amrita OBK Association. This organisation was an extracurricular activity aimed at creating equal opportunities outside public education, and did so as a mediating, supportive and inclusive system. The target group of the association was a community of disadvantaged young people, mainly of Roma origin. In the initial period, it organised career guidance counselling and various community and leisure programmes for disadvantaged Roma pupils living in the settlements of the South Transdanubian region, and later extended its activities to adult education, multicultural community programmes and the operation of vocational workshops. The organisation has established a network community as a self-help inclusive system as a peer community. A survey was carried out in 2015-2016, 20 years after the start of the guidance programme, using quantitative (documentary analysis, questionnaire with young Gypsies) and qualitative (life path interviews with young Gypsies, semi-structured interviews with young Gypsies, and a survey with young Roma) methods (structured interviews with teachers). My research research, the problem arose that the inclusive characteristics of a community or organisation which was established and functioning between 1994 and 2000, when integrated education was the main focus of my research. was a new approach and there was no discourse about inclusive environments. Despite this I would like to demonstrate that there was already an organisation in the 1990s which in its operation and activities, there was a reflection of an inclusive and mutually inclusive approach. In the context of this study, the research findings of the above-mentioned community of inclusive characteristics of the community mentioned above.